Decreasing the Dietary Ratio of Linoleic Acid (n-6) and Alpha-linolenic Acid (n-3) Does Not Reduce Adiposity or Mitigate Bone Deterioration of Obese Mice (P08-096-19). (24th October 2019) - Cao, Jay; Michelsen, Kim; Gregoire, Brian; Picklo, Matthew
Abstract: Objectives: To investigate whether the ratio of n-6: n-3 mainly as linoleic acid (LA, 18:2n-6) and alpha-linolenic acid (ALA, 18:3n-3), when ALA was kept constant, affects adiposity or adiposity-induced changes in bone structure in mice fed a high-fat diet. Since LA is a precursor for arachidonic acid which is the substrate for certain proinflammatory eicosanoids, n-6 fatty acids have been considered to promote inflammation, whereas n-3 fatty acids are considered to have anti-inflammatory properties. Studies show adiposity and inflammation are inversely associated bone mass. Therefore, we hypothesized that decreasing dietary LA content (n-6: n-3 ratio) mitigates high-fat diet (HF) induced adiposity and bone loss. Methods: Fifty-two male C57BL/6 mice at 6-wk-old were randomly assigned to 4 treatment groups ( n  = 13/group) and fed one of the diets as described in the Table below ad libitum for 6 months: a normal-fat diet (NF, 10%en) with n-6 at 6%en or HF diets (45%en) with n-6 at either 9%, 6%, or 3%en, respectively. ALA content in the diets was kept the same for all groups at 1%en, which is above the minimum requirement (0.68%en) for rodents. Diets were formulated with a combination of high oleic sunflower oil, palm oil, safflower oil and flaxseed oil to achieve desired levels of fatty acids. Results: Compared to the NF, the HF increased fat mass, percentage body fat, trabecular separation, serum bone resorption marker (tartrate-resistant acid phosphatase), and decreased bone volume/total volume ( P  < 0.05). The ratio of n-6: n-3 did not significantly affect fat mass, serum bone resorption marker, or any bone structural parameters. Conclusions: These data indicate that decreasing the dietary n-6: n-3 ratio by reducing LA intake does not reduce adiposity or improve bone structure in obese mice. Funding Sources: USDA ARS Project no. 3062-51000-053-00D. Supporting Tables, Images and/or Graphs